Problema religioznoj gramotnosti v tridcat' vos'mom slovo nazidanija Abaja - Temirkhanov, B. (Chabaršy. Dintanu serijasy, 2023)
Among the 45 words of edification of Abay Kunanbayuly, the thirty-eighth word of edification is the largest. In the content of this word of edification, one can find Arabic words, verses of the Koran, and hadiths of the Prophet Muhammad. Abay Kunanbayuly is recognized as a poet, thinker and philosopher. However, if we look at the words of Abai's edification, we will see that he was also deep in the matter of religion, and also gave his explanation of the words of God and the hadiths of the Prophet. The 38th word of Abay's edification contains important conclusions regarding religious literacy. In this study, on the basis of Abai's 38 words of edification, theological and religious views are distinguished, and the level of religious literacy in that era and the current situation are comprehensively analyzed. In his words of edification, Abay offers a measure of the level of religiosity and religious literacy of people, and this can be called Abay's own formula. Abay points out the religious shortcomings of the period in which he lived and emphasizes the importance of religious literacy. Abay tried to explain this according to the Hanafi-Maturid tradition. The 38th word of Abai's edification was used as the main source in the study.